"The Divinity School Address": Emersonian poetry and personality (Estudios Humanísticos. Filología, 1997)
In this paper we propose to consider the role played by the concepts of poetry and personality in the `Divinity School Address.' From these concepts, a clearer picture will emerge of both Emerson and nineteenth-century Unitarianism. The Divinity School Address,' far from a declaration of war on Unitarianism, was an extension of the decades long Unitarian plea for fervor from the pulpit. Far from rebelling from the Unitarian sensibility and worldview, Emerson was expanding and fulfilling it. The `Divinity School Address' presented to a very sensitive audience Emerson's building rejection of the idea of a 'personal' God. This departure hito modernism was the most radical element of the address. Emerson gradually formulated a theory of the synonymous nature of God and the soul. Mis doctrine of the soul was a doctrine of criticism, and the soul must finally be understood as the insatiable passion for the Better, which enfolded a perpetual sense of the unachieved.